Key Mutant Genes and Biological Pathways Involved in Aspirin Resistance in the Residents of the Chinese Plateau Area - Wu, Jinchun; Chang, Rong; Liu, Yanmin (Combinatorial Chemistry & High Throughput Screening, 2024)
Introduction: Aspirin is used to prevent and treat cardiovascular diseases; however, some patients develop aspirin resistance. Aim: We aimed to explore the potential molecular mechanisms underlying aspirin resistance in people living in the Chinese plateau area. Methods: In total, 91 participants receiving aspirin treatment from the Qinghai plateau area were divided into the aspirin resistance and aspirin sensitivity groups. Genotyping was performed using the Sequence MASSarray. Differentially mutated genes between the two groups were analyzed using MAfTools. The annotation of differentially mutated genes was conducted based on the Metascape database. Results and Discussion: In total, 48 differential SNP and 22 differential InDel mutant genes between the aspirin resistance and aspirin sensitivity groups were screened using Fisher’s exact test (P < 0.05). After the χ2 test, a total of 21 SNP mutant genes, including ZFPL1 and TLR3, and 19 InDel mutant genes were found to be differentially expressed between the two groups (P < 0.05). Functional analysis revealed that these differential SNP mutations were mainly enriched in aspirin resistance pathways, such as the Wnt signaling pathway. Furthermore, these genes were related to many diseases, including various aspirin indications. Conclusion: This study identified several genes and pathways that could be involved in arachidonic acid metabolic processes and aspirin resistance progression, which will provide a theoretical understanding of the molecular mechanism of aspirin resistance.
Keywords: Aspirin resistance